Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Let $k$ and $n$ be positive integers. Show that $$(k+1)^2k^2(n+1)^4-2k(k+1)n(n+1)^2(2kn+k+1)+n^2(k+1)^2$$ is a perfect square if and only if $k=n$.

share|improve this question
    
If it helps, you can reduce the polynomial modulo $k$ and $n$: $$F(k,n)\equiv n^2 \pmod k$$ $$F(k,n) \equiv (k^2+k)^2 \pmod n.$$ You can also reduce it modulo some other things, like $k^2+k$... –  anon Jul 17 '11 at 3:28
2  
Two of the terms have $(k+1)^2$ so the third must as well. Where does that come from? –  Ross Millikan Jul 17 '11 at 4:07
2  
@Ross, why must the third term have $(k+1)^2$? What if $k+1$ is a square? –  Gerry Myerson Jul 17 '11 at 6:00
add comment

2 Answers

For $k=3$ and $n=792$, $$ (k+1)^2k^2(n+1)^4-2\,k\,(k+1)\,n\,(n+1)^2(2\,k\,n+k+1)+n^2(k+1)^2=309\,396^2. $$ This is the only perfect square for $1\le k\le2\,000$, $1\le n\le10\,000$ and $k\ne n$.

share|improve this answer
    
+1, this explains why things just were not working! –  Eric Naslund Jul 17 '11 at 15:44
    
Actually, this seems quite correct. The counterexample given above is bogus, why do 9 people give it a positive rating without even checking? –  user1111929 Dec 30 '11 at 16:22
    
For $k=3,n=729$, the result is not a perfect square, but rather 74674187856 = 2^4 * 3^2 * 331 * 487 * 3217. –  r.e.s. Dec 30 '11 at 18:06
2  
@r.e.s.: 729 is a typo for 792. k=3,n=792 gives 95725884816, which is 309396^2. –  DSM Dec 30 '11 at 19:07
1  
I fixed the typo discovered by DSM (thanks to user1111929's answer). A verification with wolframalpha is here –  t.b. Dec 31 '11 at 4:16
show 2 more comments

Since Julian showed the "only if" part is not possible, here is a quick proof for the if part:

Suppose $n=k=x$. Then we have $$(x+1)^2x^2(x+1)^4-2x(x+1)x(x+1)^2(2x^2+x+1)+x^2(x+1)^2.$$ This then becomes

$$(x+1)^{2}x^{2}\left((x+1)^{4}-2(x+1)(2x^{2}+x+1)+1\right).$$ The inside term is exactly $x^{4}$ as $2(x+1)(2x^{2}+x+1)=4x^{3}+6x^{2}+4x+2.$ Hence $$F(n,n)=n^{6}\left(n+1\right)^{2}.$$

share|improve this answer
add comment

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.